Granny Fixit and the Pirate - Cadwallader, Jane (Italy ELI - Young Readers, 2009)
When Jill and Ahmed find themselves by magic in a pirate ship they meet sad pirate Bill. He has no pirate hat, treasure or parrot ! but with Granny Fixit no one stays sad for long !
Picture dictionary, games and activities.
Keywords: Adventure; Language Learning; Starter level; Story